The Habermas – Rorty Debate about Justification and Truth - Szubka, Tadeusz (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Jürgen Habermas and Richard Rorty share many philosophical commitments. However, their ways have parted when Habermas has begun to emphasize the essential or internal connection between justification and truth, and especially with its feature which may be described as unconditional or universal validity. Rorty strongly disagrees with Habermas’s contention about the essential connection between justification and truth, and puts into doubt the unconditionality claim involved in the latter notion. In this debate Habermas is arguably more convincing, but his arguments may be strengthened by pointing out that not only we do need the notion of truth over and above the notion of justification, but the notion of truth is also involved in the very notion of justification.